(untitled) - Gnap, Jozef; Sedlakova, Ivana (Doprava a spoje, 2010)
Authors deal with possibilities of assessment or calculation of forwarding fee. In practice, freight forwarder uses two ways for assessing of transportation performance. In the concrete he adds a lump sum to the transport charge or he deducts a lump sum from carriage fee. Lump sum of forwarding fee can be calculated by various methods